Collagen crosslinking in the management of advanced non-resolving microbial keratitis. Issue 8 (7th April 2014) - Shetty, Rohit; Nagaraja, Harsha; Jayadev, Chaitra; Shivanna, Yathish; Kugar, Thungappa
Abstract : Aim: To evaluate the efficacy and safety of corneal collagen crosslinking (CXL) in the management of culture proven microbial keratitis. Methods: 15 eyes of 15 patients of microbial keratitis were included in the study. Nine patients had bacterial keratitis and six had fungal keratitis. All patients underwent microbiological evaluation to identify the causative organism. The depth of the infiltrate was determined clinically with slit lamp and measured manually using anterior segment optical coherence tomography. Patients were treated with antibiotics/antifungals and those who did not respond to at least 2 weeks of topical medications underwent CXL as per the standard protocol. The same preoperative topical medications were continued post-CXL. All patients were followed up every third day and observed for signs of resolution of microbial keratitis. Results: Six of nine patients with bacterial keratitis and three of six patients with fungal keratitis resolved following CXL treatment. Patients with deep stromal keratitis or endothelial plaque failed to resolve. All patients had resolution of pain on the first postoperative day. There was an appearance of or increase in hypopyon in seven patients. No intraoperative or postoperative complications were noticed. Conclusions: CXL appears to be an effective procedure in the management of superficial microbial keratitis. It can be used as an adjunctive treatment in the management of non-resolving microbial keratitis.